Pengaruh Debt To Asset Ratio, Kepemilikan Institusional Dan Kepemilikan Manajerial Pada Kebijakan Dividen Dengan Free Cash Flow Sebagai Variabel Pemoderasi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022 - Saidah, Alvi; Rambe, Rizki Fillhayati; Arief, Muhammad (Cattleya Darmaya Fortuna, 2024)
Manufacturing companies are large-scale companies when compared to other companies so that they can make comparisons between one company and another. Manufacturing companies also have stocks that are resistant to economic crises. This is because most manufacturing products are still needed, so there is very little chance of loss. This study aims to determine the effect of Debt to Asset Ratio, Institutional Ownership, Managerial Ownership on Dividend Payout Ratio moderated by Free Cash Flow in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. The type of research used in this study is associative research. The results of the study indicate that Debt to Asset Ratio has a negative and insignificant effect on Dividend Policy, Institutional Ownership has a positive and insignificant effect on Dividend Policy, Managerial Ownership has a positive but insignificant effect on Dividend Policy, Free Cash Flow can moderate the effect of Debt to Asset Ratio on Dividend Policy, Free Cash Flow can moderate the effect of Institutional Ownership on Dividend Policy, Free Cash Flow can moderate the effect of Managerial Ownership on Dividend Policy in Manufacturing companies listed on the IDX in 2018-2022. The variables Debt to Asset Ratio, Institutional Ownership, Managerial Ownership, and Free Cash Flow are able to influence Dividend Policy by 0.148 or 14.8%, while the remaining 85.2% is influenced by other variables not examined in this study.